Global prevalence of occupational injuries among sanitation workers: a systematic review and meta-analysis - Sina Temesgen Tolera; Tesfaye Gobena; Nega Assefa; Abraham Geremew (Frontiers Media S.A., 2024)
BackgroundIn the sanitation sector, occupational injuries among sanitary workers (SWs) are prevalent due to hazardous working conditions and poor environmental surroundings. Despite the significant risks faced by these workers, the issue has received limited attention, and no comprehensive global meta-analysis on occupational injuries among sanitary workers has been conducted to date.ObjectiveIn this study, we aimed to conduct a systematic review and meta-analysis of occupational injuries among sanitary workers globally from 2000 to 2023.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines were followed for the screening process, and the Population, Intervention, Comparison, Outcome and Study (PICOS) framework was to formulate search questions. Published articles from 2000 to 2023 were retrieved using various search engines. The keywords used were as follows: "Occupation Job Injuries" *OR "Work Injuries" *OR "Occupational Injuries" AND "Sanitary workers" ("Street sweepers" [SS] *OR "health facilities cleaners" [HCFC]) *OR "Solid waste collectors" [SWCs] *OR "Sewage workers" [STW] were used. Data analysis was performed using Stata Version 17MP. The overall effect size was calculated using the random-effects model combined with the restricted maximum likelihood (REML) approach, known as the Random-Effect REML Model. A 95% confidence interval (CI: 95%) was applied, and a p-value of less than 0.05 was considered statistically significant.ResultsStudies were sourced from PubMed (n = 34), Medline (n = 39), Embase (n = 23), Global Health (n = 37), other databases (n = 54), and review studies (n = 10), resulting in a total of 197 studies. Of these, only 23 studies fully met the inclusion criteria. Among 8,138 sanitary workers (SWs), 4,469 (55%) were solid waste collectors (SWCs), 2,317 (28%) were street sweepers (SS), 1,144 (14%) were health facility cleaners (HCFC), and 208 (3%) were a combination of SS and SWCs. Globally, the pooled prevalence of occupational injuries among SWs was 36.49% (95%CI: 0.29-0.45). Specifically, 39.14% (95%CI: 0.24-0.53) prevalence was observed in high-income countries, while 35.22% (95%CI: 0.36-0.44) was reported in low-income countries. Year-by-year analysis showed a prevalence of 36.70% (95%CI:0.28-0.46) from 2001 to 2015 and 36.45% (95% CI:0.25-0.48) from 2016 to 2022. The overall heterogeneity of the studies was substantial, with an I-squared value of 90.03% and a heterogeneity index of 214.43 (p < 0.05), indicating statistically significant heterogeneity among the eligible studies.ConclusionThis systematic review and meta-analysis revealed that sanitation and hygiene workers face an increased risk of occupational injuries, largely due to insufficient attention to occupational safety and health services in their work environments. To mitigate these risks, the review recommends policy amendments, national regulations, and international initiatives aimed at improving occupational health and safety (OHS) services for these workers. These measures are crucial for reducing the prevalence of work-related injuries in the sanitation sector.